MODELS, TENDENCIES AND EVERYDAY LIFE IN THE EARLY STAGES OF THE PENITENTIARY OF SANTIAGO, CHILE. 1843-1860 - Monteverde Sánchez, Alessandro (2017)
During the early decades of the 19th century, Chile engaged in a significant political debate regarding the reform of its nascent penitentiary and punitive system. The goal was to eliminate itinerant imprisonment and address the internal issues of the country's jail facilities. Central to this reform was the moral rehabilitation of criminals through a structured penitentiary treatment. This treatment combined two main elements: a modular confinement system within a panoptical building governed by absolute silence, and a regimen blending religious instruction with labor in internal workshops. The reform was inspired by penitentiary models from the United States and Europe, developed in the late 18th and early 19th centuries. Chile’s political and intellectual elite supported these changes, promoting the initiative through debates, reports, and proposals. Their efforts culminated in the 1843 law establishing the Penitentiary of Santiago. This article offers a historical analysis of that initial phase of reform, focusing on the type of penitentiary treatment implemented in the Santiago facility. It contrasts these reformist ideals with documentary records detailing the internal regime and daily operations of the prison between 1858 and 1860, during the administration of Waldo Silva Algüe, a key figure in the evolution of Chile's prison system.